2013
DOI: 10.3329/bjas.v42i2.18505
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status of buffalo farmers and the management practices of buffaloes in selected areas of Bagerhat District of Bangladesh

Abstract: The study was conducted to investigate the socio-economic status of the buffalo farmers and the management practices of buffaloes at different villages of Boraikhali, Hoglabunia and Khawlia union of Morrelgonj upazilla in Bagerhat district of Bangladesh. A total of 60 respondents (20 from each union) were randomly selected from three unions. The data was collected through personal interviewing with pre-tested questioner. The investigation revealed that buffalo rearing was practiced by the middle (30-40 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 1 publication
4
29
1
Order By: Relevance
“…Incidence of diseases is a major constraint of livestock production which not only reduces the productivity but also causes economic loss. Mitra et al, (1995), Sarker et al, (2013) and Gupta et al, (2014) also reported that a serious threat of infectious diseases like FMD, HS and BQ in animals were the main problem. Hence, proper support is required for vaccination against some epidemic viral and bacterial diseases for their prevention and control.…”
Section: Major Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Incidence of diseases is a major constraint of livestock production which not only reduces the productivity but also causes economic loss. Mitra et al, (1995), Sarker et al, (2013) and Gupta et al, (2014) also reported that a serious threat of infectious diseases like FMD, HS and BQ in animals were the main problem. Hence, proper support is required for vaccination against some epidemic viral and bacterial diseases for their prevention and control.…”
Section: Major Diseasesmentioning
confidence: 99%
“…Like study areas of Bagerhat districts in Bangladesh majority of the farmers were fully dependent on grazing (Sarker et al, 2013). Majority of the respondents kept their buffaloes mainly with extensive system and bathan and very little percentage of the farmer practiced semiintensive system in the study areas.…”
Section: Availability Of Feeds Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The annual food and cloth purchasing capacity of the buffalo farmers were found to be increased to 62.85 and 58.33%, respectively. Considering all this parameters related to livelihood, it was clearly found that the socioeconomic status of the buffalo farmers was improved through buffalo rearing although the management practices need to be improved with scientific approaches [10].…”
Section: Literature Reviewmentioning
confidence: 99%